Evaluation of cardiac output by 5 arterial pulse contour techniques using trend interchangeability method. Issue 25 (June 2016) - Fischer, Marc-Olivier; Diouf, Momar; Wilde, Robert B.P. de; Dupont, Hervé; Hanouz, Jean-Luc; Lorne, Emmanuel
Abstract : Abstract: Cardiac output measurement with pulse contour analysis is a continuous, mini-invasive, operator-independent, widely used, and cost-effective technique, which could be helpful to assess changes in cardiac output. The 4-quadrant plot and the polar plot have been described to compare the changes between 2 measurements performed under different conditions, and the direction of change by using different methods of measurements. However, the 4-quadrant plot and the polar plot present a number of limitations, with a risk of misinterpretation in routine clinical practice. We describe a new trend interchangeability method designed to objectively define the interchangeability of each change of a variable. Using the repeatability of the reference method, we classified each change as either uninterpretable or interpretable and then as either noninterchangeable, in the gray zone or interchangeable. An interchangeability rate can then be calculated by the number of interchangeable changes divided by the total number of interpretable changes. In this observational study, we used this objective method to assess cardiac output changes with 5 arterial pulse contour techniques (Wesseling's method, LiDCO, PiCCO, Hemac method, and Modelflow) in comparison with bolus thermodilution technique as reference method in 24 cardiac surgery patients. A total of 172 cardiac output variations were available from the 199 data points: 88 (51%) were uninterpretable, according to the first step of the method. The second step of the method, based on the 84 (49%) interpretable variations, showed that only 18 (21%) to 30 (36%) variations were interchangeable regardless of the technique used. None of pulse contour cardiac output technique could be interchangeable with bolus thermodilution to assess changes in cardiac output using the trend interchangeability method in cardiac surgery patients. Future studies may consider using this method to assess interchangeability of changes between different methods of measurements. Abstract : Supplemental Digital Content is available in the text